PSXV-14 Level of spontaneous oxidative modification of sperm plasma proteins in stallions of different ages. (8th October 2021) - Atroshchenko, Mikhail; Engalycheva, Mariya; Shitikova, Anna
Abstract: The objective of the study was to assess the level of spontaneous oxidative modification of sperm plasma proteins (OMP) in young and mature stallions as indicators of the severity of oxidative stress. Sperm from 12 stallions aged 14–18 years (average age 15.8±1.9 years) (Group I) and 12 stallions aged 3–5 years (average age 4.3±0.6 years; Group II) was obtained during the breeding season (February-May). Each ejaculate was evaluated by volume, concentration, total number of spermatozoa, as well as by the progressive motility and survival of spermatozoa in diluted sperm during its hypothermic storage at +4°C. For a quantitative assessment of the OMP level, a spectrophotometric analysis of 2, 4-dinitrophenylhydrazones formed during the interaction of carbonyl derivatives of proteins with 2, 4-dinitrophenylhydrazine was carried out (SF-2000, Russia). The level of aldehyde- and ketone-dinitrophenylhydrazones of neutral (ADNPHn, KDNPHn) and basic (ADNPGb, KDNPGb), and the total level of OMP (S OMP) was measured. Significance of differences was assessed by the Mann-Whitney test, the results were statistically significant at P ≤ 0.05. The total level of spontaneous OMP of sperm plasma in aged stallions is statistically significantly higher than in young stallions (531.7 and 384.3 Uod/g protein, respectively, P < 0.05). This indicates a higher degree of oxidative stress in Group I, a more significant damage to the amino acid residues of sperm plasma proteins. In Group I a shift in the absorption spectrum towards neutral aldehyde derivatives (367.6 and 255.8 Uod/g protein, respectively, P < 0.05) was noted. We assume that the pro-oxidant systems in a stallion body increasingly prevail over the protective ones with the age. This leads to an increase in the level of OMP in the sperm and a decrease in the survival of spermatozoa during the hypothermic storage of diluted sperm. Authors acknowledge financial support from Russian Science Foundation, Grant No: 20-16-00101.